2010
DOI: 10.1590/s1415-43662010001100004
|View full text |Cite
|
Sign up to set email alerts
|

O relevo na interpretação da variabilidade espacial dos teores de nutrientes em folha de citros

Abstract: RESUMOA diagnose foliar é um critério para avaliação do estado nutricional das culturas agrícolas, que auxilia na compreensão da fertilidade do solo e na aplicação racional de adubos, levando em conta aspectos econômicos e ambientais. O trabalho teve como objetivo utilizar as formas do relevo como regra para auxiliar na interpretação da variabilidade espacial dos teores de nutrientes da folha de citros. Coletas de folhas foram realizadas em intervalos regulares de 50 m, totalizando 332 pontos de amostragem. Os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Worsham et al (2010) also found that semivariograms fit to these two models when the carbon and N levels in the plant litter were studied under different forest cover. Some studies show that the levels of mineral nutrients in the tissue of the plants usually fit to spherical and exponential models (VIEIRA et al, 2010;LEÃO et al, 2010;CAVALCANTE et al, 2011;RODRIGUES JÚNIOR et al, 2011). The fitted models exhibited high determination coefficients (R 2 ) that ranged from 0.92 to 0.99 and low squared residual sums (SRSs) ( Table 3).…”
Section: A Coefficient Of Variation Lower Than 35%mentioning
confidence: 99%
“…Worsham et al (2010) also found that semivariograms fit to these two models when the carbon and N levels in the plant litter were studied under different forest cover. Some studies show that the levels of mineral nutrients in the tissue of the plants usually fit to spherical and exponential models (VIEIRA et al, 2010;LEÃO et al, 2010;CAVALCANTE et al, 2011;RODRIGUES JÚNIOR et al, 2011). The fitted models exhibited high determination coefficients (R 2 ) that ranged from 0.92 to 0.99 and low squared residual sums (SRSs) ( Table 3).…”
Section: A Coefficient Of Variation Lower Than 35%mentioning
confidence: 99%
“…When studying morphological components of Marandu grass in places with different levels of pasture degradation, Silva Neto et al (2012) found that the values fitted spherical and exponential semivariogram models. Some studies have shown that mineral nutrient concentrations in the tissue of plants commonly fit spherical and exponential models (VIEIRA et al, 2010;LEÃO et al, 2010;CAVALCANTE et al, 2011;RODRIGUES JÚNIOR et al, 2011). The fitted models showed high coefficients of determination (R 2 ), ranging from 0.80 to 0.99, and low residual sums of square (SS r ).…”
Section: Coefficients Of Variation Lower Than 35%mentioning
confidence: 99%
“…When studying morphological components of Marandu grass in places with different levels of pasture degradation, Silva Neto et al (2012) found that the values fitted spherical and exponential semivariogram models. Some studies have shown that mineral nutrient concentrations in the tissue of plants commonly fit spherical and exponential models (VIEIRA et al, 2010;LEÃO et al, 2010;CAVALCANTE et al, 2011;RODRIGUES JÚNIOR et al, 2011). The fitted models showed high coefficients of determination (R 2 ), ranging from 0.80 to 0.99, and low residual sums of square (SS r ).…”
Section: Coefficients Of Variation Lower Than 35%mentioning
confidence: 99%